Private lending and debt risks of low-income developing countries - Bruno Bonizzi; Christina Laskaridis; Jesse Griffiths (Overseas Development Institute (ODI), 2020)
Low-income developing countries (LIDCs) are greatly affected by the coronavirus pandemic, and sovereign debt has become a major concern. The International Monetary Fund (IMF) already classified 44% of LIDCs as being in debt distress or at risk of it before the Covid-19 crisis began. One major feature of the current situation, which is unlike previous episodes of LIDC debt problems, is the extent of borrowing from private sources. This report is a timely investigation into the risks that this new wave of private borrowing may cause for LIDCs. It draws three major conclusions for LIDCs and the international community in the coming years when debt issues are likely to dominate their economic policy-making: 1. The costs and availability of borrowing are linked to global financial conditions, and therefore solutions that focus on domestic adjustment are misdirected, especially in the context of the global health emergency. 2. The fact that developing countries have borrowed extensively from international private creditors will complicate debt-restructuring efforts, and introduces several minefields on the road ahead. 3. Standstills and debt restructurings must be comprehensive and include private as well as public creditors if they are to work for all countries.
Keywords: 330